2019
DOI: 10.1080/23723556.2019.1575691
|View full text |Cite
|
Sign up to set email alerts
|

Falling from grace: HPRT is not suitable as an endogenous control for cancer-related studies

Abstract: HPRT is a housekeeping enzyme involved in recycling guanine and inosine in the purine salvage pathway. As a housekeeping gene, HPRT has been widely used as an endogenous control for molecular studies evaluating changes in gene expression. Yet, recent evidence has shown that HPRT exhibits high variability within malignant samples. We designed this study to determine whether this observed upregulation is consistently found, therefore rendering hprt an unsuitable normalization control in cancer. Utilizing protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…HPRT1 is considered a housekeeping gene and is widely used as an endogenous control in gene expression studies; however, recent studies, including our data, have revealed its potential involvement in cancer [ 3 , 4 , 5 ]. Unchecked and aberrant exponential cell growth, a hallmark of cancer, results in increased transcriptional output related to cancer genes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HPRT1 is considered a housekeeping gene and is widely used as an endogenous control in gene expression studies; however, recent studies, including our data, have revealed its potential involvement in cancer [ 3 , 4 , 5 ]. Unchecked and aberrant exponential cell growth, a hallmark of cancer, results in increased transcriptional output related to cancer genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although widely considered to be a housekeeping gene, recent studies have shown HPRT1 expression levels to be highly variable between malignant and normal tissue, suggesting that it is unreliable as an endogenous control in cancer-related studies [ 3 ], and also indicating its plausible role in cancer biology. HPRT1 expression levels varied widely in a large cohort of both normal and malignant samples of different tissue origin, with breast cancer exhibiting the highest average HPRT1 compared to other malignancies [ 4 ]. Studies from various cancers, such as colorectal cancer, have shown elevated levels of HPRT1 in tumor samples compared to normal tissues [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypoxanthine guanine phosphoribosyltransferase (HPRT) is a key enzyme in salvage pathway responsible for the formation of GMP and IMP by recycling guanine and inosine from degraded DNA and RNA, respectively 26 . To maintain cellular GTP level in somatic cells, HPRT is reliably expressed in low level 27 . Unlike in normal cells, recent study showed that HPRT expression is highly variable in various cancer tissues including lung, breast, colon, prostate and pancreas 27 .…”
Section: Introductionmentioning
confidence: 99%